TINJAUAN YURIDIS TERHADAP PERLINDUNGAN PENGGUNA GO-JEK YANG DIRUGIKAN TERKAIT PERETASAN DATA PRIBADI MELALUI APLIKASI GOJEK (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Consumers who need products often before they start making transactions are required to provide complete information about their identity or company (if the consumer is a company). There are at least two potential risks that befall Go-jek users, among others, are the risk of consumer data security and the risk of transaction errors. From the background of the problem, the formulation of the problem was born, namely, first How is the legal protection against Go-jek users who are harmed in connection with the hacking of personal data through the Go-Jek application account? Second, How can consumers resolve efforts related to hacking personal data?This research is a type of research that is normative, which more specifically discusses the principles of law. Research on the principles of law aims to find the legal principle of the application of a positive law. The approach used is the approach of legislation, which is an approach that is carried out by studying all laws and regulations related to the problems (legal issues) that are facing. In this study, the data source used is secondary data with primary, secondary, and tertier legal materials conducted by way of literature studies.From the results of the research obtained that, first, the protection of gojek consumer law is based on legislation, namely; Law No. 8 of 1999 on Consumer Protection on the principles of benefits, balance, justice, security and certainty realized by the form of accountability by gojek parties. In addition, the legal protection of gojek consumers is also based on Law No. 11 of 2008 on Information and Electronic Transactions, regulation of the Minister of Communication and Informatics Number 20 of 2016 concerning the Protection of Personal Data Through Electronic Systems. Second, legal consequences of hacking, namely not fulfilling consumer rights, liability for compensation for business actors, sanctions and disputes. The author's advice, in order to better maintain personal data in media accounts, businesses further improve the security of their electronic systems and the government to immediately issue specific regulations related to the protection of consumer personal data.Keywords: Personal Data-Protection-Consumer Go-Jek